In Remembrance of Holy and Martyr Prince Constantin Basarab Brâncoveanu – A Commemoration of 310 Years Since his Death - Radu Ştefan VERGATTI (Annals: Series on History and Archaeology (Academy of Romanian Scientists))
Prince Constantin Basarab Brâncoveanu, a member of the Cantacuzino family, was raised and educated by it. He found himself in this situation as orphan of father since infancy. In his youth, up to the age of 20, he already knew the Greek, Latin and Slavonic languages​​well. He read a lot. He was in charge of printing the monumental Bible in Romanian, a work requested and patronized by his uncle, prince Şerban Cantacuzino. After he himself became ruler of Valachia (October 28, 1688) he was concerned with the fertilization and population of the Bărăganu Plain, with the construction of cities, where he left great monuments (Craiova, Bucharest, Făgăraş), monumental palaces, representative of the relationship between man and nature (Mogoşoaia, Potlogi, Obilesti). He also built the largest Orthodox monasteries in Wallachia (Hurezi, Sâmbăta, Sf. Gheorghe Nou), and developed the Princely Academy (Academia Domnească) bringing it to the level of a "Faculty of Arts" in the universities of Western Europe. He also developed a royal chancellery with connections in Europe, Central Asia and North Africa, etc. In time, he amassed a huge fortune, which made Sultan Ahmet III (1703-1730) and the Grand Vizier Ali Paşa want to take his money. His assassination, together with his four sons and his relative the boyar I. Văcărescu, led to the creation of the image of a martyr for the Romanian people and their faith. The Library of the Romanian Academy preserves several Romanian manuscripts containing verses and songs of anonymous bards, who took over and spread over time through folklore the legend of the martyrdom of the Voyvode and his sons.